Research on Real-time Performance of Aperiodic Message and OptimizedDesign of Bandwidth Allocation in Multifunction Vehicle Bus - ZHU Jun; LI Fang; WANG Li-fang (机车电传动)
By analyzing the characteristics of every type of messages, two bandwidth allocation strategies of MVB aperiodic communicationwere proposed , and relevant formula was derived. In combination with the scheduling principles of aperiodic messages, theoptimized bandwidth allocation strategy were researched and compared. The real-time performance of aperiodic messages had greatlyimproved after the optimization of bandwidth allocation.